A assistência estudantil no contexto da "reforma" do ensino superior público no Brasil: um estudo da assistência estudantil da UFS a partir da implantação do PNAES - Melo, Maria Rosângela Albuquerque (2013)
This thesis is addressing the Student Assistance Policy in the context of reform of public higher education. The study analyzed the changes after the institutionalization of PNAES in IFES, through the operationalization of the UFS student assistance. The survey consisted of bibliographic and documentary, with emphasis on the dimension qualiquantitaiva, exploratory and descriptive, guided by the perspective of dialectical and historical materialism. As a problem to be solved, wondered if the UFS could effect a policy of student assistance as provided in PNAES. Regarding the general objective aimed to verify whether there were changes in the student assistance PROEST after the institutionalization of PNAES in UFS. As data sources were used in institutional documents, being prioritized Management Reporting and Accountability of UFS and CODAE / PROEST the years 2008 to 2012, but others were also analyzed, such as resolutions, laws, tables historical and institutional budgets. The study allowed us to analyze the trends and characteristics of the student assistance after the institutionalization of PNAES in UFS. Realized that the obstacles in effecting a policy of student assistance are directly linked to the priorities defined in the midst of neoliberal policies, in which hegemony is markets, also associating the student assistance to the service logic and not of law. Therefore, the steps taken to seek compliance with pre-set targets by REUNI who will play in PNAES. The survey results show that the policy of student assistance is an important mechanism for ensuring students´ rights. Let obvious difficulties for establishing a policy of assistance in the form of a public policy, as provided in PNAES. In view of this it must be stated that there were no significant changes in welfare policy implemented by PROEST / UFS after deployment PNAES.